THE MICROSTRUCTURES OF HYDROXYAPATITE POWDER FROM PRECIPITATION METHOD IN DIFFERENT SOLUTION - Ratih Langenati; Basril Abbas; Widjaksana Widjaksana; Basuki Agung Pudjanto; Nusin Samosir (Jurnal Sains Materi Indonesia, 2007)
THE MICROSTRUCTURES OF HYDROXYAPATITE POWDER FROM PRECIPITATION METHOD IN DIFFERENT SOLUTION. Biomaterial is conceptually defined as a bioactive material which can undergo chemical reactions in the body only at its surface and the surface reactions lead to bonding of the tissues at the interface. From the requirements point of view, one of the prospective biomaterials is hydroxyapatite sometimes called hydroxylapatite (HA) with a chemical formula of Ca10(PO4)6(OH)2. In the present study we used calcium hydroxide and phosphoric acid as the Ca2+ and PO4 3- source, while water and synthetic body fluid (SBF) solutions as parameter. Microstructure characterization of the synthesized HA powders was performed using Scanning/Scanning Transmission Electron Microscopy (SEM/STEM) and Fourier Transformed Infra Red (FT-IR) Spectrometry. From the micrographs, it shows that the HApowder from water solution has a rounded shape and the diameter of about 100 nm. The other HA powder using SBF solution shows needle like shape and the elongation is about 50-100 nm. Different powder drying method applied in the HA synthesizing exhibit difference micrographs especially for HA from SBF.